Unveiling the Unseen: Mutashabihat on Eschatology and the Limits of Human Cognition in Qur'anic Exegesis - Hasan, Abdur Rokhim; Ikhwan, Masrur; Umar, Ahamad; Herwan (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study explores the interpretation of mutashabihat eschatological verses in the Qur'an, focusing on the evolving approaches of classical and modern exegetes. Classical scholars, such as Al-Ṭabarī and Al-Rāzī, predominantly employed tafwīḍ (submission of meaning), acknowledging the limits of human cognition regarding the ultimate reality of these verses. In contrast, modern exegetes like Quraish Shihab and Ibn ‘Āshūr have increasingly adopted ta’wīl (symbolic interpretation), offering deeper moral and spiritual insights while still preserving the Qur'anic messages. The study analyzes a purposive sample of mutashabihat eschatological verses, including those describing the Day of Judgment, Paradise, Hell, and eschatological concepts such as aṣ-Ṣirāt (the bridge) and al-Mīzān (the scale). The analysis identifies key trends in the interpretation of these verses, highlighting the shift from literal to symbolic readings and emphasizing the pedagogical role of eschatological imagery. This study contributes to the existing literature by providing a comprehensive examination of the transition from tafwīḍ to ta’wīl in the interpretation of eschatological verses and offering insights into how these interpretations can inform modern Islamic pedagogy. The implications of this study are significant for both scholarly engagement with Qur'anic exegesis and the teaching of ulūm al-Qur'an (sciences of the Qur'an), encouraging a flexible, contextually relevant approach to interpreting eschatological verses in light of contemporary theological and educational concerns.